America the fair again : using brain science to create a more just nation - Meegan, Dan, 1968- (Ithaca : Cornell University Press, 2019)
"This book is about the increasing polarity of American politics written by a cognitive scientist whose work investigates the situations that cause people to feel as if they have been treated unfairly. Why have conservatives and liberals been unable to find any common ground on problems relating to economic well-being and inequality? Liberals look with envy at other nations whose citizens enjoy as rights what many Americans view as privileges: health care, maternity leave, a robust unemployment insurance plan, and postsecondary education. It's been assumed that America is exceptional in this regard because it has a culture of selfishness while other nations have cultures of selflessness, in which middle-class citizens are happy to subsidize those earning less. This book suggests instead that these nations thrive because the middle class selfishly enjoys the same benefits as everyone else. One is less likely to worry about being on the short end of redistribution when one has a low-risk standard of living. The American Left has lost sight of the possibility that the middle class can be sold on the personal benefits of an increased role for government in protecting its citizens"--
Introduction : from carnage to Canada -- That's not fair! -- Blind spots -- Oh, the inequity! -- Double down -- Getting to know you -- Declaration of interdependence.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
JSTOR
Keywords: Fairness -- Social aspects -- United States; Fairness -- Political aspects -- United States; Polarization (Social sciences) -- United States -- History; Social conflict -- United States -- History; Impartialité -- Aspect social -- États-Unis.; Impartialité -- Aspect politique -- États-Unis.; Polarisation collective -- États-Unis -- Histoire; POLITICAL SCIENCE -- Essays; POLITICAL SCIENCE -- Government -- General; POLITICAL SCIENCE -- Government -- National; POLITICAL SCIENCE -- Reference; POLITICAL SCIENCE -- Commentary & Opinion; Polarization (Social sciences); Social conflict; United States; History